Stilistic analysis and social value in andrea hirata's novel ordinary people (review through a literature sociology approach) - Jenumi Faidis; Missriani Missriani; Yessi Fitriani (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
Stylistic Analysis and Social Values in Andrea Hirata's novel Orang-Orang Asli (Review Through the Sociology of Literature Approach) is an analysis of the use of language and the relationship between literary works and society in the novel. This research is a descriptive qualitative study with the aim of describing the uniqueness and selection of vocabulary, particularly the use of diction (choice of words), figurative meaning (figurative meaning) and social values contained in the novel Orang-Orang Asli by Andrea Hirata. The data of this research are in the form of lingual units which contain unique vocabulary and morphosyntax as well as uniqueness of language style and social values. Data collection techniques using library techniques, observe and take notes. Data analysis techniques are flow analysis which consists of four activities that occur simultaneously, namely data collection and classification, data reduction, data presentation, and drawing conclusions. Furthermore, this study uses the theoretical triangulation method, meaning that the discussion of the problem is the discussion of the problem by using some data to obtain the same data. The results of this study indicate that the use of diction or choice of words in Andrea Hirata's novel Orang-Orang Asli is (1) denotation meaning, (2) connotation meaning, (3) synonymous words (4) antonyms (5) concrete words, (6) Abstract, (7) general words (8) special words (9) straightforward words, (10) narrowing and broadening of the meaning (11) active words and (12) amelioration and peryorasi words. Utilization of a figurative language style that is unique and creates aesthetic effects on readers, namely metaphor, simile, metonemia, synekdoke, allegory, climax and correction. The social values contained in the novel Orang-Orang Asli by Andrea Hirata are the social values of love which include love and affection, help to help, devotion, care. The value of responsibility includes empathy, discipline. Life harmony values include obligation, tolerance and cooperation. The analysis above shows that the writer is able to highlight the uniqueness of the selection and use of specific vocabulary and figurative language which is aesthetically pleasing and has social values. This uniqueness is motivated by social and educational factors of the author. This has resulted in a distinctive style that has become a special characteristic of Andrea Hirata in expressing his ideas through the novel Orang-Orang Asli.